2022
DOI: 10.3390/antiox11081477
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Oxidative Stress in Obstetrics and Gynaecology—A Systematic Literature Review

Abstract: Oxidative stress has been implicated in many diseases, including reproductive and pregnancy disorders, from subfertility to maternal vascular disease or preterm labour. There is, however, discrepancy within the standardized markers of oxidative stress in obstetrics and gynaecology in clinical studies. This review aims to present the scope of markers used between 2012 and 2022 to describe oxidative stress with regard to reproduction, pregnancy, and pregnancy-related issues. Despite the abundance of evidence, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 100 publications
0
1
0
Order By: Relevance
“…An array of markers is employed to describe OS, encompassing MDA, nitric oxide (NO), ROS, TAC, total antioxidant activity (TAA), SOD, GPx, glutathione peroxidase-4 (GPx4), glutathione reductase (GR), LPO, 8-hydroxydeoxyguanosine (8-OHdG), oxidized glutathione (GSSG), CAT, superoxide (O 2 -), paraoxonase (PON-1), oxidative stress index (OSI), high-sensitivity C-reactive protein (hs-CRP), 8-iso-prostaglandin F2α (8-iso-PGF2α), prostaglandin F2α (PGF2α), GSH, and glutathione transferase (GST). These markers are analyzed using various materials, primarily blood (serum or plasma) and placenta, along with urine, Wharton's jelly mesenchymal stem cells derived from the umbilical cord, and saliva [189,190].…”
Section: Biomarkers Of Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation

Oxidative Stress in Pregnancy

Grzeszczak,
Łanocha-Arendarczyk,
Malinowski
et al. 2023
Biomolecules
“…An array of markers is employed to describe OS, encompassing MDA, nitric oxide (NO), ROS, TAC, total antioxidant activity (TAA), SOD, GPx, glutathione peroxidase-4 (GPx4), glutathione reductase (GR), LPO, 8-hydroxydeoxyguanosine (8-OHdG), oxidized glutathione (GSSG), CAT, superoxide (O 2 -), paraoxonase (PON-1), oxidative stress index (OSI), high-sensitivity C-reactive protein (hs-CRP), 8-iso-prostaglandin F2α (8-iso-PGF2α), prostaglandin F2α (PGF2α), GSH, and glutathione transferase (GST). These markers are analyzed using various materials, primarily blood (serum or plasma) and placenta, along with urine, Wharton's jelly mesenchymal stem cells derived from the umbilical cord, and saliva [189,190].…”
Section: Biomarkers Of Oxidative Stressmentioning
confidence: 99%
“…Therefore, the authors suggest that TOS and TAS levels may serve as additional markers for the diagnosis and assessment of the clinical severity of NVP. In addition, Drejz et al [189], based on an analysis of 83 selected papers, recommend the establishment of a common core panel of OS markers to be used in all studies related to OS in obstetrics and gynecology. They suggest including ROS as a direct marker of OS, 8-OHdG as a marker of DNA/RNA damage, and MDA as a marker of LPO.…”
Section: Biomarkers Of Oxidative Stressmentioning
confidence: 99%

Oxidative Stress in Pregnancy

Grzeszczak,
Łanocha-Arendarczyk,
Malinowski
et al. 2023
Biomolecules
“…Therefore, markers such as malondialdehyde (MDA), lipid peroxidation (LPO), advanced oxidation protein products (AOPP), and 8-OHdG are commonly used to assess oxidative damage. Michalina et al compiled studies from 2012 to 2022 in the field of female reproduction and identified the most commonly used oxidative stress markers in female reproduction as ROS, 8-OHdG, MDA, TAC, and glutathione (GSH) [21]. Research by Iman et al suggested that oxidative stress biomarkers such as 8-OHdG, TAC, and MDA are associated with reproductive hormones and ART pregnancy outcomes, potentially serving as valuable tools for evaluating clinical characteristics in IVF patients [22].…”
Section: Oxidative Stress Biomarkers In Follicular Fluidmentioning
confidence: 99%
“…Important examples of the latter include polycystic ovary syndrome (PCOS) and endometriosis, conditions that signal organ dysfunction associated with infertility risk. The pathophysiology of the most important obstetric complications including preeclampsia (PE), gestational diabetes mellitus (GDM) and intrauterine growth restriction (IUGR) nearly always involves placental OS; in addition, oxidant vs. antioxidant imbalance with oxidant predominance also increases the risk for habitual abortion and premature delivery [17][18][19].…”
Section: Markers Of Oxidative Stress In Obstetricsmentioning
confidence: 99%